'I‐shaped' sign in the upper mediastinum: a novel potential marker for antenatal diagnosis of d‐transposition of the great arteries. (28th May 2013) - Ishii, Y.; Inamura, N.; Kawazu, Y.; Kayatani, F.; Arakawa, H.
ABSTRACT Objectives To investigate the 'I‐shaped' sign as a novel echocardiographic marker for antenatal diagnosis of d‐transposition of the great arteries (dTGA) in routine cardiac examination, and to compare its prevalence in fetuses with dTGA, those with other congenital heart diseases (CHDs) and those with normal structural hearts. METHODS This retrospective evaluation involved 1134 fetuses undergoing echocardiography to screen for CHD over a 4‐year period. I‐shaped sign was defined as the characteristic appearance of the aortic arch, resembling the letter 'I', from the most anterior to the most posterior point of the descending aorta visible in the three vessels and trachea view. The frequency of this sign was evaluated in cases with dTGA, those with other cardiac defects and those with normal cardiac structures. Results CHD was diagnosed in 671 (59.1%) cases, of which 31 (4.6%) had dTGA. I‐shaped sign was observed in 30/31 (96.8%) cases of dTGA, compared with 31/640 (4.8%) cases with other cardiac anomalies, which included single ventricle with pulmonary atresia or severe pulmonary stenosis, hypoplastic left heart syndrome with aortic atresia, corrected transposition of the great arteries, and double outlet right ventricle with malposition of the great arteries. I‐shaped sign was detected significantly more frequently in the dTGA group compared with the normal group and with the other CHDs group (both P < 0.001) and had 96.8% sensitivity and 97.1% specificity for diagnosis of dTGA. Importantly, I‐shaped sign was never observed in fetuses with structurally normal hearts. Conclusions Detection on echocardiography of an extremely long vessel with a marked I‐shape should raise suspicion of cardiac anomaly, especially dTGA. This marker may therefore aid in the prenatal diagnosis of dTGA during routine ultrasound examination. Copyright © 2012 ISUOG. Published by John Wiley & Sons Ltd.